QÎMAH KITÂB SIBAWAIH WA JUHÛD AL-LUGHAWIYYÎN AL-‘ARAB AL-MU’ÂSHIRÎN - Milah, Aang Saeful (Syarif Hidayatullah State Islamic University of Jakarta, Indonesia, 2019)
There are some reasons that appeal me to do research on contemporary linguists’ contributions to Sībawaih’s al-Kitâb. As a pioneer on Arabic linguistics book, al-Kitâb has been the starting point for the classic linguists to study linguistics phenomena. And so are the contemporary linguists. For the later, they place the book in the first raw of references, be it by taking instant benefits from the fundamentals it contains or by keen reading on it. In fact, some efforts conducted by the linguists after Sībawaih can be regarded to as attempts to comprehend his theories, as well as to explain aspects which are still ambiguous to some others. This is what can be understood from the abundance varieties of works produced by later linguists: they criticize the book; they give commentaries, they give preliminary fundaments on further readings on it; they study on the theories; they explain the sources; and they trigger to study the construct of Sībawaih’s thoughts. From these various studies, even if they refer to the same book (al-Kitâb), it can be grasped that the linguist do not meet an agreement one and others in comprehending Sībawaih’s words. In this piece of paper, I try to describe what contemporary linguists do with the al-Kitāb, and how the link it to their theories. After all, this can be regarded as their contributions to the book in developing linguistics theories in a wider context.